Criminal and Civil Legal Protection for Female Students as Victims of Sexual Violence in Islamic Boarding Schools - Widodo, Guntarto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Sexual violence against female students in Islamic boarding schools constitutes a serious violation of human rights and reveals structural deficiencies in legal protection within religious-based educational institutions. This study examines the scope and effectiveness of criminal and civil legal protection for female students as victims of sexual violence in Islamic boarding schools in Indonesia. The research employs a normative juridical method, using statutory, conceptual, and case approaches. Primary legal materials include the Indonesian Criminal Code, Law No. 12 of 2022 on the Crime of Sexual Violence, Law No. 35 of 2014 on Child Protection, and regulations concerning witness and victim protection. The case approach focuses on the Decision of the Central Java High Court Number 238/PID.SUS/2025/PT SMG, which affirmed the conviction of a pondok pesantren caretaker for committing sexual violence against female students and imposed both imprisonment and restitution obligations. The case illustrates that criminal legal protection in Indonesia predominantly emphasizes punitive sanctions against perpetrators, reflecting a retributive justice orientation. However, the implementation of civil legal protection, particularly victims’ rights to restitution, compensation, and long-term psychological recovery, remains limited and inconsistently enforced. The study finds that unequal power relations, institutional protection of perpetrators, and social stigma continue to hinder victims’ access to comprehensive justice. This research concludes that effective legal protection requires an integrated framework combining criminal accountability, civil liability of perpetrators and educational institutions, and a victim-centered recovery approach, supported by strengthened state supervision over Islamic boarding schools to ensure substantive justice for female students.